The Baduy Indigenous Community And The Utilization Of Information Technology - Yuliasari, Ika; Elizabeth, Novianty; Junaidi, Ahmad (Jurnal Komunikasi, 2024)
The Baduy indigenous community consists of the Inner Baduy and Outer Baduy residents, with their settlement area in Kanekes Village, Leuwidamar District, Lebak Regency, Banten. The cultural norms of Sunda Wiwitan prohibit Baduy residents from adopting modern values in areas such as education, healthcare, and Information technology. However, the current communication reality contradicts the customary rules, as Outer Baduy residents use Information technology to support activities in agriculture, trade of agricultural products, and marketing of handicrafts. The purpose of the study is to describe and analyze the phenomenon of the use of communication technology by the Baduy community. The ethnography of communication method is used to find the reality of interaction, practice and communication patterns. The Baduy indigenous community interacts with consumers through digital communication platforms. This reality can be reviewed from the perspective of symbolic interactionism and marketing communication. The research was undertaken employing a qualitative approach and utilizing the method of virtual ethnography analysis. Data collection was conducted through direct observations within the Baduy community settlements, in-depth interviews with selected informants, engaging in Focus Group Discussions (FGDs), documentation of information content disseminated through social media platforms, as well as capturing photographic evidence. The application of the virtual ethnography method encompassed an analytical examination of the intricacies of communication realities, exploration of the roles assumed by communication actors, meticulous crafting of virtual messages, and an in-depth exploration of the utilization patterns observed in the realm of social media. The results showed that the communication behavior of the Baduy Kaduketuk Luar community is an adaptation of a mediated communication system. The use of communication technology media is done autodidactically. marketing communication is carried out by advertising, direct marketing to agents, social media publications, face-to-face communication, and word of mouth marketing.